The comparative study of the postoperative in exodontics using the laser and without using the laser (Research, Society and Development, 2022)
To compare the effects of photobiomodulation with and without laser exposure at wavelengths 660 nm and 808nm in post-surgical wounds, as to its efficacy in the aspects of biostimulation, analgesia, anti-inflammatory. Methodology: The sample consisted of 20 patients requiring extraction in different arcades, totaling 20 extractions. The population was inserted in two groups, A and B in which one of the groups was applied to laser therapy and the other group without the application of laser therapy, according to a pre-established protocol and with the knowledge of patients to the procedures to be performed. Also applied a visual analog scale (VAS) and numerical visual scale (EVN) to record the degree of analgesia of these patients. Results: The results showed a decrease in painful symptomatology for the experimental group and a satisfactory postoperative period. Final Considerations: Laser for therapeutic purposes is an easy-to-handle and well-feasible tool in the routine of dental clinics. It can be used to control postoperative pain in exodontia.